OUTSOURCING DALAM MANAJEMEN SUMBER DAYA MANUSIA - Amruzziyad; Sahwi; Mohamad Iwan Fitriani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study employs a quantitative approach using a survey method through questionnairedistribution to analyze the impact of outsourcing practices in Human ResourceManagement (HRM) on satisfaction and performance. The data analysis technique usedis multiple linear regression. The findings indicate that outsourcing is a strategy used bycompanies to enhance efficiency, reduce costs, and focus on core activities. Effectiveimplementation requires a systematic process, including needs analysis, careful selectionof qualified service providers, clear contract negotiation, and continuous monitoring ofservice execution. Additionally, compliance with labor regulations and the protection ofemployee rights are essential considerations. When applied properly, HR outsourcing candeliver significant strategic benefits to organizations.